Effect of Addition of Sugarcane Bagasse Activated Charcoal (Saccharum officinarum L) on Reducing Peroxide Numbers in Cooking Oil - Farah Fajarna; Erva Reyhani; Safrida Kemala Putri (STIE AAS Surakarta, 2022)
A research has been conducted entitled